Understanding Turkey's Kurdish Question. - Bilgin, Fevzi.
1 online resource (219 pages)
Keywords: This book, comprising chapters by leading experts, delves into the complicated nature of Turkey's Kurdish issue. Contributors discusses the evolution of Kurdish nationalism, the contemporary Kurdish movement and its violent legacy, civil society efforts in Turkey's Kurdish region, and the international dimensions of the Kurdish question.